2021
DOI: 10.3390/ijms22041585
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophins Time Point Intervention after Traumatic Brain Injury: From Zebrafish to Human

Abstract: Traumatic brain injury (TBI) remains the leading cause of long-term disability, which annually involves millions of individuals. Several studies on mammals reported that neurotrophins could play a significant role in both protection and recovery of function following neurodegenerative diseases such as stroke and TBI. This protective role of neurotrophins after an event of TBI has also been reported in the zebrafish model. Nevertheless, reparative mechanisms in mammalian brain are limited, and newly formed neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 127 publications
0
15
0
Order By: Relevance
“…Zebrafish have become a prominent vertebrate model for studying diseases [ 36 , 37 ] since they have 82% orthologues of human disease-associated genes [ 37 ]. Recent evidence affirms that zebrafish represent a novel suitable model to study Alzheimer’s disease [ 38 ], Huntington’s disease [ 39 ], traumatic brain injury [ 32 , 40 ], and sensory organs’ diseases, especially blindness and deafness. Among factors involved in those pathologies is the BDNF/TrkB axis.…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish have become a prominent vertebrate model for studying diseases [ 36 , 37 ] since they have 82% orthologues of human disease-associated genes [ 37 ]. Recent evidence affirms that zebrafish represent a novel suitable model to study Alzheimer’s disease [ 38 ], Huntington’s disease [ 39 ], traumatic brain injury [ 32 , 40 ], and sensory organs’ diseases, especially blindness and deafness. Among factors involved in those pathologies is the BDNF/TrkB axis.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that the reasons why some patients experience long-term sequelae in these domains, while others do not, is not well understood and requires further research. Further, there are no drugs currently available to treat TBI [49,50]. However, previous preclinical studies of drugs have shown positive signs when patients diagnosed with mTBI receive drug therapies for more than 12 h. Thus, future clinical trials may want to test the efficacy of drug therapies on functional outcomes such as return to work or recovery [50].…”
Section: Discussionmentioning
confidence: 99%
“…Further, there are no drugs currently available to treat TBI [49,50]. However, previous preclinical studies of drugs have shown positive signs when patients diagnosed with mTBI receive drug therapies for more than 12 h. Thus, future clinical trials may want to test the efficacy of drug therapies on functional outcomes such as return to work or recovery [50].…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical and clinical studies have also demonstrated a pharmacological value of NGF in the treatment of neurotrauma outcomes ( Kromer, 1987 ; Cacialli, 2021 ). The rationale behind these studies does not necessarily include the effect of NGF on cholinergic neurons, but extends to other peculiarities of the biological action of NGF.…”
Section: An Extended Rationale For the Use Of Ngf In Diseases Of The Central Nervous Systemmentioning
confidence: 99%